A Juridical Analysis of Court Decision Number 92/Pdt.Sus-HKI/Copyright/2024/Commercial Court at the Central Jakarta District Court (Copyright Infringement Case Involving Agnes Monica) - I Gusti Ngurah Deva Aditya Laksmana Putra; Maidah Purwanti; Masdar Bakhtiar (Fakultas Hukum Universitas Djuanda, 2026)
This study aims to analyze the determination of legal subjects and the legal consequences of Court Decision Number 92/Pdt.Sus-HKI/Copyright/2024/PN Niaga Jkt.Pst regarding the copyright infringement of the song